Research on NC Milling Process of Worm Gears based on Generating Method - Hongyu Han; Aijing Li; Leijie Wang; Yingliang Yu (Jixie chuandong)
In order to realize the generating machining of worm gears， the worm gear hob is used on the NC transformed ordinary milling machine. The proportional relationship between the rotation of one turn of the worm gear hob and the rotation of one tooth of the worm gear workpiece is realized by extending the function of thread instruction and taper thread instruction. By distributing the allowable cumulative error of worm gear pitch evenly on several arcs of worm gear pitch circle， the accuracy of worm gear pitch and transmission is greatly improved， and thus the transmission stability is improved. The practice shows that this method not only achieves high machining accuracy of worm gears， but also expands the application range of NC transformation.